Douze minutes avant minuit : l’effet « graphic novel » du chapitrage dans Watchmen - Alain Boillat (Cahiers de Narratologie)
This study aims to discuss the status and functions of chaptering—and more generally the arrangement of thresholds—in comics, based on the study of the famous graphic novel Watchmen (1986-1988). We propose to discuss the explicit mention of « chapters » and its implications on the structure and consumption of Watchmen. The retrospective designation of Watchmen episodes as « chapters » is, in our opinion, one of the manifestations of the emergence of a new editorial context that has since emerged with the omnipresence of graphic novels in generalist bookshops. The substitution of the general title of the series by the number of a specific chapter is, in our opinion, emblematic of the meaning that chaptering can have in a medium such as comics, both strongly overlapped with serial practices, and driven, since the 1970s and 1980s, by a quest for artistic legitimacy. Through the analysis of all the graphical elements of chapter segmentation, we will see that in the history of the comic book, Watchmen is indeed one of the main publications to have paved the way for the integration of chapters in this medium of expression.